Writing Essentials - Rodrigues, Dawn. (New York W. W. Norton and Company, Inc., 1996)
A quick reference guide to writing essays online, research writing, MLA and APA documentation, basic document design, sentences and words, grammar, punctuation, and mechanics. Pages have color tabs which help to highlight major topics.
Keywords: Writing